The Impact of Electronic Medical Record Use on Doctors In Hospitals: Scoping Review - Sani Khoirul Amalia; Cahya Tri Purnami; Farid Agushybana (GLOBAL HEALTH SCIENCE GROUP, 2025)
Electronic medical records (EMR) are an information technology innovation that has been adopted in various health facilities to improve operational efficiency and quality of health services. In addition to its benefits, the use of EMR also presents a number of challenges for doctors in hospitals. This study aims to evaluate the positive and negative impacts of EMR use on doctors in hospitals. This study used a scoping review method using the PRISMA guideline, and produced 13 articles that met the inclusion criteria related to the impact of EMR on doctors in hospitals. The results of the study showed that EMR had a positive impact on improving efficiency, quality of care, and patient safety, but also increased the administrative burden. The use of EMR outside of working hours increases the risk of burnout and decreases satisfaction with work-life balance. In addition, doctor-patient interaction can be reduced, and concerns about data privacy reduce patient openness. Hospitals need to optimize workflows, provide comprehensive and ongoing training, delegate administrative tasks to non-clinical staff and develop more user-friendly EMR systems. This is important to ensure that EMR technology can support improved quality of care without sacrificing doctor well-being and interaction with patients.